Toward sustainable waste management: assessing factors affecting single-use plastic reduction in the Southern Region of Malaysia - Mohamad Sofian Abd Rahim; Azwani Alias; Nurezdiani Said; Siti Norliyana Harun; Noorashikin Md Noor (Penerbit Universiti Kebangsaan Malaysia, 2024)
In response to the urgent need for enhanced waste management practices, a study was undertaken to identify factors influencing the effectiveness of a single-use plastic reduction program in the Sothern part of Malaysia. By 2030, Malaysia has set an ambitious target to phase out single-use plastics, as outlined in the Roadmap Towards Zero Single-Use Plastics 2018-2030. However, the roadmap lacks a clear and unified strategy, relying on state governments and stakeholders to align their efforts. This lack of strategic cohesion represents a critical research gap, particularly regarding the role of local stakeholders, such as food hawkers, whose participation is essential for the program's success. In this context, the pivotal role of food hawkers in ensuring the success of such programs cannot be overstated. A survey involving 149 respondents was conducted to analyze knowledge, attitudes, and practices related to single-use plastic reduction. Descriptive analysis, Cronbach's alpha, Likert scale analysis, and Pearson correlation were employed to achieve the research objectives. The findings reveal that knowledge significantly influences attitudes towards single-use plastic reduction, with a strong correlation observed between the two variables. Additionally, socio-demographic characteristics such as age, education level, and income, exhibit notable disparities in factors associated with single-use plastic reduction. In conclusion, addressing knowledge gaps emerges as a critical aspect of effective single-use plastic reduction initiatives. Moreover, tailored interventions considering socio-demographic diversity are essential for comprehensive program success.